2020
DOI: 10.5761/atcs.oa.19-00156
|View full text |Cite
|
Sign up to set email alerts
|

Stable Hemodynamics within “No-Touch” Saphenous Vein Graft

Abstract: Purpose: To investigate the hemodynamics characteristics of the "no-touch" saphenous vein graft (SVG) conduits by nicardipine intraluminal administration in vivo experiment. Methods: A total of 59 consecutive patients were enrolled and underwent a sequential SVG to three non-left anterior descending (LAD) targets with the average runoff ≤2 mm, 30 with "no-touch" harvest technique (group A) and 29 with conventional preparation (group B). The patients were subject to nicardipine intraluminal injection during off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Jiang et al reported that N-SVG was associated with higher MGF than C-SVG, and this was the result of less spastic features and less intimal endothelium damage due to the SVG harvest procedure and intraluminal pressure. 13 , 21) More MGF are associated with higher graft velocity, which contributes to increased shear stress, endothelial nitric oxide synthase, and other shear stress-dependent factors, especially in the intimal endothelium-preserved N-SVG. 16 , 21) These mechanisms may lead to less spastic graft and intimal thickening regression, i.e., anti-atherosclerotic effect, and provide short- and long-term patency comparable to those of arterial grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al reported that N-SVG was associated with higher MGF than C-SVG, and this was the result of less spastic features and less intimal endothelium damage due to the SVG harvest procedure and intraluminal pressure. 13 , 21) More MGF are associated with higher graft velocity, which contributes to increased shear stress, endothelial nitric oxide synthase, and other shear stress-dependent factors, especially in the intimal endothelium-preserved N-SVG. 16 , 21) These mechanisms may lead to less spastic graft and intimal thickening regression, i.e., anti-atherosclerotic effect, and provide short- and long-term patency comparable to those of arterial grafts.…”
Section: Discussionmentioning
confidence: 99%
“… 8) The mechanism behind good graft patency and the exact means of preventing the VGD remain controversial, but multiple factors have been proposed. 9 13) …”
Section: Introductionmentioning
confidence: 99%
“…47 It has been shown that the no-touch harvesting technique is associated with higher baseline blood flow and pressure-tolerant capacity after nicardipine intraluminal administration during off-pump CABG procedures compared with conventional preparation. 48 The no-touch technique may improve both short-and long-term SVG patency by reducing intimal hyperplasia and atherosclerosis progression. 10,49 Samano et al randomized 54 patients undergoing CABG to either the conventional or the no- Unique identifier: NCT03501303) will give further insights on the outcomes of the no-touch technique compared with conventional harvesting.…”
Section: No-touch Techniquementioning
confidence: 99%
“…Multiple preoperative and perioperative strategies are under investigation to improve SVG patency. Isolation strategies for harvesting SVG have been tested in randomized clinical trials including the no-touch technique versus conventional preparation methods [7,14]. The notouch protocol, in which fat and surrounding tissue is not cleared from the vessel, aims to preserve the vasa vasorum and nerves in the adventitia to reduce vascular spasm, neointima, and atherosclerosis [15].…”
Section: Introductionmentioning
confidence: 99%